2017
DOI: 10.1016/j.ijrobp.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Training, Refinement, and Validation of a Knowledge-based Planning Quality-Control System for Radiation Therapy Clinical Trials

Abstract: Purpose To demonstrate an efficient method for training and validation of a knowledge-based planning (KBP) system as a radiotherapy clinical trial plan quality control (QC) system. Methods We analyzed 86 stage IB-IVA cervical cancer patients treated with intensity modulated radiotherapy (IMRT) at two institutions according to XXXXX multi-institutional protocol standards. The protocol utilized a planning target volume (PTV) and two primary organs-at-risk (OARs): pelvic bone marrow (PBM) and bowel. Secondary O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 23 publications
0
88
0
Order By: Relevance
“…This work suggests that closed‐loop reoptimization of the new candidate is beneficial before the incorporation, to avoid introducing suboptimal plans into the knowledge base. Our solutions of updating the training library with improved plans may better preserve the anatomical variety, which distinguished our work from Li's work where poor plans were filtered 37. To avoid unacceptable geometric outliers, statistical verification assisted by Model Analytics38 can be helpful, where plans with Z‐scores > 3.5 were reviewed case‐by‐case.…”
Section: Discussionmentioning
confidence: 99%
“…This work suggests that closed‐loop reoptimization of the new candidate is beneficial before the incorporation, to avoid introducing suboptimal plans into the knowledge base. Our solutions of updating the training library with improved plans may better preserve the anatomical variety, which distinguished our work from Li's work where poor plans were filtered 37. To avoid unacceptable geometric outliers, statistical verification assisted by Model Analytics38 can be helpful, where plans with Z‐scores > 3.5 were reviewed case‐by‐case.…”
Section: Discussionmentioning
confidence: 99%
“…Both intensity modulated radiotherapy (IMRT) and volumetric modulated arc therapy (VMAT) are advanced technologies that have been commonly used for treatment of prostate cancer . However, there may be large variations in the quality of the treatment plans due to differences in both experience and skill of the treatment planners.…”
Section: Introductionmentioning
confidence: 99%
“…Such differences may limit the desired organs‐at‐risk (OAR) sparing and the target coverage that can be achieved. Recent investigations have demonstrated that knowledge based planning (KBP), which utilizes a library of previously treated patient plans, has enormous potential for improving the quality and consistency of treatment plans …”
Section: Introductionmentioning
confidence: 99%
“…Several studies [63][64][65][66][67] have carried out to explore the utilization of KBTP approach for treatment plan generation in radiotherapy. The current scientific research and available commercial products for KBTP are limited to predicting DVHs within accepted ranges [14].…”
Section: Knowledge-based Treatment Planningmentioning
confidence: 99%